2014
DOI: 10.7314/apjcp.2014.15.13.5171
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Vacuum-Assisted Core Biopsy Results for Non-Palpable Breast Lesions

Abstract: Background: The increase in breast cancer awareness and widespread use of mammographic screening has led to an increased detection of (non-palpable) breast cancers that cannot be discovered through physical examination. One of the methods used in the diagnosis of these cancers is vacuum-assisted core biopsy, which prevents a considerable number of patients from undergoing surgical procedures. The aim of this study was to present the results of stereotactic vacuum-assisted core biopsy for suspicious breast lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Whereas the same ratios for the core biopsy have been obtained as 97% and 94% respectively (Pisano et al, 1998;Leifland et al, 2003;Willems et al, 2012). This suggests the higher efficiency of core biopsy in the diagnosis of non-palpable lesions in the aspect of higher sensitivity and specificity (Agacayak et al, 2014).…”
Section: Discussionsupporting
confidence: 56%
“…Whereas the same ratios for the core biopsy have been obtained as 97% and 94% respectively (Pisano et al, 1998;Leifland et al, 2003;Willems et al, 2012). This suggests the higher efficiency of core biopsy in the diagnosis of non-palpable lesions in the aspect of higher sensitivity and specificity (Agacayak et al, 2014).…”
Section: Discussionsupporting
confidence: 56%
“…According to previous reports, the incidence of ecchymosis is 2.2%, and the incidence of hematoma ranges from 0.8% to 1.1%. 20,21 The incidence of infection is extremely low (0.0%–0.1%). 21,22 In the present study, no patients had infections.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 The incidence of infection is extremely low (0.0%–0.1%). 21,22 In the present study, no patients had infections. Ten patients had various degrees of bleeding; one had bleeding from the puncture site and nine had 2- to 4-cm subcutaneous ecchymoses.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of diagnosis, these lesions have good prognosis, as in malignancies detected with screening. However, it is important to use the diagnostic criteria appropriately for the identification of lesions in this category and for the evaluation of their stability (23). Some studies dealing with the pathological results of cases which were categorized as BI-RADS 3 but had a cancer diagnosis showed that short delays in the diagnosis of lesions in this group had negligible effects on the prognosis (24).…”
Section: Discussionmentioning
confidence: 99%